Mineralogical Composition and Origin of Airborne Dust in an Alpine Environment of Hochtor (Hohe Tauern, Austria): Effects on Pedogenesis, Biological Soil Crusts, and Vascular Plant Growth - Peer, Thomas; Zheng, Ling-Juan; Neubauer, Franz; Friedl, Gertrude; Hauzenberger, Christoph; Kasper-Giebl, Anne (Frontiers in Earth Science, 2022)
Mineral dust has a significant impact on alpine ecosystems. Notwithstanding this, knowledge in this field is limited. We investigated (a) the mineralogical composition of dust components at Hochtor (Hohe Tauern, Austria), (b) the effects of mineral dust in the formation of soil and biological soil crusts (BSCs), and (c) how plant communities respond to dust input in this interdisciplinary study. Mineral particles such as silicates, carbonates, oxides, volcanic quartz phenocrysts, opaque ore minerals, and spheres, such as micrometeorites and fly ash aggregates, were detected using a scanning electron microscope (SEM) equipped with an energy dispersive X-ray spectrometer (SEM-EDX). Rare micrometeorites are of extraterrestrial origin (cosmic dust) and the decorated spheres are aggregates of fly ashes from anthropogenic origin. In terms of size, fine particles (<100 µm) and coarse particles (>100 µm) characterize the dust composition, originating mainly from adjacent rock outcrops, while the transport from the North African desert appears to be less important and diluted by local sources. The research was carried out as part of the pan-European biodiversity project "Soil Crusts International" (SCIN). The results suggest that mineral dust aids in the rapid formation of BSCs in highly disturbed treated plots, and thus, both fine sand and available phosphorus are statistically proven to be determinants of the rapid growth of biocrusts. The number of plant individuals also increases between 2016 and 2020, however at a relatively moderate rate due to permanent mechanical erosion and debris flow within the treatment plots. Silica dust is believed to be a contributing factor to the widespread distribution of silicate plants in limestone habitats, such as Primula minima and Cerastium uniflorum, two ‘acidophilic' species that have been tested more closely. Finally, it is deduced that 1) aeolian dust plays a role in the continuous process of soil and crust formation, and 2) it works as a growth regulator in complex biological communities such as BSCs and vascular plant communities by creating new habitats and increasing biodiversity.